Chemical Composition, Pasting, and Thermal Properties of 22 Different Varieties of Peas and Lentils. Issue 3 (1st November 2016) - Li, Chongjun; Ganjyal, Girish M.
Abstract : Eleven green pea, five yellow pea, and six lentil varieties were analyzed for their composition and pasting and thermal properties. Lentils had higher protein content (25.8–28.6%) than peas (22.2–27.6%). However, peas had higher fiber content (19.8–31.4%) than lentils (17.8–21.8%). Both peas and lentils showed similar starch content (41.5–52.3 and 43.5–50.0%, respectively), and they were both low in fat (<1.6%). Micro‐Visco‐Amylograph tests showed C‐type amylograph patterns, except for Richlea variety. Thermal properties of flours were measured at 20, 40, 60, and 80% moisture content with a differential scanning calorimeter. Linear trends with a decrease in peak temperatures ( T p ) were observed with an increase in moisture from 20 to 60%, and beyond 60% T p was constant. Currently, peas and lentils are sold by mixing different varieties into classes based on the similarities in color and size of the seeds. However, significant differences were observed in chemical compositions and pasting and thermal properties among varieties tested. This suggests that it may be a good practice to use single varieties or group varieties based on their composition and functional properties, so that the end user may have a consistent final product when using the peas.